Investigating Flexibility as a Performance Dimension of a Manufacturing Value Modeling Methodology (MVMM): A Framework for Identifying Flexibility Types in Manufacturing Systems - Bürger, Niklas; Demartini, Melissa; Tonelli, Flavio; Bodendorf, Freimut; Testa, Chiara; et al. (Procedia CIRP, 2017)
In recent years manufacturing companies have been faced with various challenges related to volatile demand and changing requirements from customer as well as suppliers. This trend is now even accelerating with a direct impact on the value chain. New technological roadmaps and suggested interventions in manufacturing systems try to solve these challenges and solutions such as the German high tech strategy “Industrie 4.0” or the Italian cluster “Fabbrica Intelligente” which often aimed at enhancing the flexibility of manufacturing systems among many other competitive dimensions. However, these approaches often do not provide a detailed definition of flexibility and its different manifestations. Therefore, the question rises if different types of flexibility, that have an impact on the complete manufacturing system, can be better identified with the existing Manufacturing Value Modeling Methodology (MVMM). This question becomes even more important when considering the potential that smart machines interacting with humans, such as cyber-physical systems (CPS), and the possibility to increase connectivity and data access through technologies, such as the internet of things (IoT), offer for increasing flexibility. Especially due to the various possibilities it becomes even more important to understand, which kind of flexibility is needed for a given problem. Implementing flexibility into the MVMM requires a ‘catalog’ that makes use of the MVMM framework presenting an overview of internal and external influence factors in order to support the identification of correct solutions and improvements related to functional areas in the manufacturing environment. Starting from a qualitative literature review on manufacturing flexibility, a ‘flexibility catalog’ is designed, which provides a structural definition of existing flexibility types and their composition as well as providing decision support. In conclusion, the scope of the ‘flexibility catalog’ is to verify that the flexibility demand fits into the market trends and is aligned to the manufacturing and company strategy, in order to help firms to take decisions and delivering valu
Keywords: value modeling creation; manufacturing flexibility; Industry 4.0